Penerapan Mesin Teknologi Tepat Guna Penggiling Bumbu Pecel Kapasitas 5 Kg/Jam Bagi UMKM Sambi Kerep Surabaya - Siswadi, Siswadi; Riyadi, Slamet; Nugroho, Wahyu (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2022)
Indonesia is a tropical country with a very strategic geographical location. Therefore, Indonesia has a variety of delicious culinary delights to serve. Pecel is a culinary dish that has a long history in Indonesian history. Pecel is a favorite food of the Indonesian people, so the number of pieces traders is vast in several areas today. It is making relatively traditional peace seasoning that has inspired researchers to produce appropriate technology products for pecel grinders with a capacity of 5 kg/hour with an electric power of 0.2 kW, which is needed as big as for SMEs in the Sambi Keep area of Surabaya. This TTG machine can increase the amount of pecel seasoning production capacity.